The Effectiveness of Phonological Awareness Training in Treating Deficiencies in Auditory Processing Among Children with Learning Disabilities Among Elementary Cycle Students in Saudi Arabia - Khasawneh, Mohamad Ahmad Saleem; Alkhawaldeh, Mohammad Abedrabbu (International Journal of Language Education, 2020)
This study aimed at identifying the effectiveness of using a phonological awareness-based instructional program in developing the phonetic sequential-memorization skill among students with learning disabilities in the Aseer region. The study sample consisted of forty students from the third, fourth, fifth, sixth, and seventh grades, selected from schools in the Directorate of Education in the Aseer region. The sample was diagnosed by the special education teacher as having learning disabilities. The study used the quasi-experimental methodology and divided the sample into an experimental group and a control group. After applying the instructional program, the results showed that the experimental group outperformed the control group in acquiring the phonetic sequential-memorization skill. The results showed no statistically significant differences in the phonetic sequential-memorization skill due to the difference of grade. It is concluded that the instructional program has a continuing effect in developing the phonetic sequential-memorization skill among students with learning disabilities in the Aseer region.